Understanding the association between milk yield with major milk constituents and somatic cell count in Jersey crossbreds - Swarnalata Bara; Saroj Kumar Chaurasia; Rashmilata Rakesh; Bhuneshwar Pal Singh Kanwar; H C Yadav; N K Dahiya; Bhupender Singh; Sunita Patel; Das, Ajoy (Indian Journal of Dairy Science, 2025)
In the dairy industry, understanding the correlation between somatic cell count (SCC), milk constituents and milk production is essential for optimizing milk production, ensuring milk quality, and maintaining cow health. Studying relationships among them can guide dairy farmers to enhance the productivity of their animals by making informed decisions thus improving food and nutritional security. The study found correlations between test day milk yield with SCC, total solids, Solid Not Fat (SNF), lactose, protein, and fat as -0.233, -0.092, -0.056, -0.131, and 0.092 respectively. Protein and lactose content showed a significant, inverse relationship with milk yield, with correlation coefficients below zero (P<0.01). However, total solids, fat content, and SNF displayed a weaker, non-significant negative correlation with milk yield. Moreover, test-day milk yield and SCC also exhibited a significant negative (P<0.05) correlation. These results indicate that lower protein and lactose levels, along with higher SCC, are associated with reduced milk yield, indicating the importance of managing these factors to optimize dairy production and enhance the overall quality of the milk.